Ecological Model Explaining the Psychosocial Adaptation to COVID-19 - Gaspar, Tânia (2022)
Funding Information: Gina Tom? is a Post DOC Funda??o Ci?ncia e Tecnologia. Concei??o Pereira, Maria Augusta Machado, Susana Moreira, Alexandra Carreiro, Aurora Lino and Ana Bernardo (Linde Saude) provided sleep disorder patients. Rute de Sousa was an important liaison with the Portuguese Psychologists Association. We are thankful to the following professional Associations for the disseminating and for promoting the surveys among their members, namely the Portuguese Medical Association (Ordem dos M?dicos), Portuguese Nurses Association (Ordem dos Enfermeiros), Portuguese Psychologists Association (Ordem dos Psic?logos Portugueses). We thank the endorsement of the WASM (World Association of Sleep Medicine), ESRS (European Sleep Research Society), and APS (Associa??o Portuguesa de Sono). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.